Investigation of resistive random-accesss memory (RRAM) materials and devices - Sim, Wei Kiat (2019)
An advancement in the current technology is pushing for better technological memory devices in terms of performance and reliability. As the current technology such as DRAM and FLASH memory is reaching its limits in its technology to scale down, other forms of technology are required to overcome this limitation. Hence, there is the development of emerging memory devices such as phase-change memory (PCM) and resistive random-access memory (RRAM) and spin-transfer torque random-access memory (STT-RAM). RRAM possess the most potential in terms its scalability and properties among all the emerging memory devices. In this paper, a few different RRAM devices that are made with different metal oxide with the same top and bottom electrodes are fabricated and have its properties tested. Out of the oxides tested, hafnium oxide seems to be the one metal oxide that has promising properties for use in an RRAM device.